Aplicabilidade da arbitragem na incorporação imobiliária - Bezerra, Eudes Vitor (2012)
The objective of this study is to elucidate the main features of the Arbitration and its effective application in Real Estate Incorporations. In this vein, it is emphasized that the scope and determine the applicability and deployment of the use of arbitration in relation to the Real Estate Incorporations, including establishing the advantages and disadvantages of the use of arbitration in these real estate transactions. It is feasible to say that a democratic state must protects the right of choice of citizens in relation to conflict resolution, when such rights are available and stamp sheet, ie, the use of arbitration in real estate development is optional and is not required. Thus, one who seeks means to resolve disputes arising from real estate developers can relinquish jurisdiction and make use of arbitration. However, it is a requirement sine qua non, the observance of the autonomy of the parties, failing to invalidate the use of arbitration